Evaluation of Community-Based Tourism Development in Nagari Tuo Pariangan - Ayang Khairunnisa; Alhilal Furqan; Naufal Hibatullah; Fernando Fasandra; Fadlul Rahman (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2025)
Nagari Tuo Pariangan is an area in West Sumatra that maintains Minangkabau traditions. This area is believed to be the place where the Minangkabau civilization began. The unique geographical condition is an added value for Nagari Tuo Pariangan to become one of the priority tourism destinations in Tanah Datar Regency. This research aims to evaluate tourism development in the village based on the CBT stage framework prepared by the Asia Pacific Economic Cooperation (APEC) and uses a qualitative approach. Based on the study's results, community-based tourism development in Nagari Tuo Pariangan can be categorized as a developing CBT because it almost fulfils every stage of development in CBT, even though each stage in community-based tourism development is not fully optimized, and there is still much to be addressed. The development stage of CBT implementation in Nagari Tuo Pariangan is at the stage of market demand and marketing strategy. The stage that has not been carried out at this time is monitoring and evaluation. This study can show the advantages that make it an example for other regions and the shortcomings in optimizing Nagari Tuo Pariangan tourism.